The Biological Relevance of NHERF1 Protein in Gynecological Tumors - Sonnessa, Margherita; Sergio, Sara; Saponaro, Concetta; Maffia, Michele; Vergara, Daniele; Zito, Francesco Alfredo; Tinelli, Andrea (Frontiers in Oncology, 2022)
Gynecological cancer management remains challenging and a better understanding of molecular mechanisms that lead to carcinogenesis and development of these diseases is needed to improve the therapeutic approaches. The Na+/H+ exchanger regulatory factor 1 (NHERF1) is a scaffold protein that contains modular protein-interaction domains able to interact with molecules with an impact on carcinogenesis and cancer progression. During recent years, its involvement in gynecological cancers has been explored, suggesting that NHERF1 could be a potential biomarker for the development of new targeted therapies suitable to the management of these tumors. This comprehensive review provides an update on the recent study on NHERF1 activity and its pathological role in cervical and ovarian cancer, as well as on its probable involvement in the therapeutic landscape of these cancer types.